Synthesis, spectroscopic characterization and antibacterial screening of novel N-(benzothiazol-2-yl)ethanamides - Obasi, Lawrence Nnamdi; Ukoha, Pius O.; Chah, Kennedy F.; Anaga, Aruh O. (Eclética Química, 2011)
Synthesis, electronic, infrared, elemental micro analytical studies were carried on N-(benzothiazol-2-yl)trichloroethanamide [4] and N-(benzothiazol-2-yl)chloroethanamide [5]. They were also screened in vitro and in vivo for antibacterial activity. The results indicate that the compounds are very stable and that they show high antibacterial activities against both grampositive and gram-negative bacteria tested. Both derivatives of 2-aminobenzothiazole were active against the multiresistant bacteria with IZD ranging from 9 -18 mm [5] and 9 – 20mm [4]. From the MIC results it is observed that the [5] derivative produced a better antibacterial activity than the [4] derivative. The lethal concentrations (LC50) of the compounds were also determined. Their solubilities and melting points were also determined.